ANALISIS EFISIENSI MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR PERKEBUNAN YANG TERCATAT PADA BURSA EFEK INDONESIA - B31112147, ARIE HARDI (Jurnal Manajemen Update, 2014)
Working capital is one of the most important factors in managing the company, because of this working capital financing implemented throughout the company's operations so that it can be said that the working capital is the "lifeblood" of the company. Good working capital is an efficient working capital levels where the faster-moving inventories. The faster turnover of capital the higher the company's performance and impact on profitability will increase. This study aimed to analyze the effect of working capital on profitability efficient plantation sub-sector company listed on the Indonesia Stock Exchange, and the data of this study are secondary data and taken as many as 35 years of data by taking the 7-year study from 2006 to 2012 in 5 companies and obtained from Indonesia Stock Exchange. Indicators used in the efficiency of working capital is the cash conversion cycle, by analyzing the current liquidity and leverage ratio by analyzing the debt ratio, while the indicators used to calculate the profitability is Return on Assets. Methods of data collection and data analysis is documentation by using multiple linear regression. The results showed a partial cash conversion cycle is not a positive effect on the profitability of significance of 0.779 which is greater than 0.05, while for liquidity and leverage gained significance value amounted to 0,037 to 0,000 for liquidity and leverage, and the second result is smaller than 0.05 so that it can be concluded liquidity and leverage negatively affect profitability. Simultaneously working capital efficiency is proxied by the cash conversion cycle, liquidity and leverage have significant effect on profitability. Â  Keywords: working capital efficiency, profitability